التغيرات في المواقف الدولية من اتفاقية السلام ( مشاكوس ) - عبد الرحيم عبدالقادر (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
We have dealt in this research to the agreement was a junction in the history of Sudan’s political and which was the impact of stopping that bloody civil war that tore Sudan in general and to South Sudan in particular and hence its importance, the peace agreement (Naivasha) in Kenya in Machakos, which we touched on, in a search distributed to four demands in addition to the introduction and conclusion dealt with the text of the agreement and the location of the contract in addition to the international, Arab and regional position of the agreement with the dimensions of the agreement On Sudan’s political future.